2009
DOI: 10.1021/ma901453x
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Properties and Polymorphic Behavior of Isotactic Poly(1-Butene) from Metallocene Catalysts: The Crystallization of Form I from the Melt

Abstract: A study of the crystallization from the melt and of the polymorphic behavior of isotactic poly(1-butene) (iPB) prepared with metallocene catalysts is presented. Samples of isotactic polybutene of different stereoregularity, containing different concentrations of stereodefects (rr triads defects) and regiodefects (4,1 units) have been prepared with different C 2 -and C 1 -symmetric metallocene catalysts. The concentration of defects and the molecular mass are controlled through a rational choice of the catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
189
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(196 citation statements)
references
References 53 publications
6
189
1
Order By: Relevance
“…Among the previous characterizations, only DSC detected a large difference in the T m s (T m ¼130 1C for form I and 80-95 1C for form I¢). 33,42 This result provided direct evidence that form I¢ and I are different polymorphs. It was suggested from a large difference in their T m s that form I¢ is structurally disordered form I.…”
Section: Polymorphismmentioning
confidence: 58%
See 2 more Smart Citations
“…Among the previous characterizations, only DSC detected a large difference in the T m s (T m ¼130 1C for form I and 80-95 1C for form I¢). 33,42 This result provided direct evidence that form I¢ and I are different polymorphs. It was suggested from a large difference in their T m s that form I¢ is structurally disordered form I.…”
Section: Polymorphismmentioning
confidence: 58%
“…Very recently, De Rosa et al 33 reported that the low isotacticity sample directly crystallizes into form I¢ from the melt state. Here the stereoregularity effects on lamellar thickness /lS were investigated.…”
Section: Mobility Effects On Lamellar Thicknessmentioning
confidence: 99%
See 1 more Smart Citation
“…24 ■ RESULTS AND DISCUSSION Mechanical properties. The polymorphic transformation occurring in i-PBu upon storage fresh (form II) samples at room temperature is associated with profound changes in the mechanical response of the material.…”
Section: Methodsmentioning
confidence: 99%
“…The parameter R takes into account the differences in the diffraction power of the two families of planes, and it has been estimated equal to 0.36. 24 The amorphous halo has been determined from WAXD pattern of an atactic poly(1-butene) sample. The resulting weight fraction of form I is considered in the following discussion on transformation kinetics.…”
Section: Methodsmentioning
confidence: 99%